ANALISIS STRATEGI PEMASARAN ERIGO STORE BRAND FASHION LOKAL INDONESIA YANG MENDUNIA - Rivani Fardiana Putri; Elsa Windu Fitriani; Sri Hardianti Sartika (Transpublika Publisher, 2022)
In doing business, business actors must be able to keep up with the times so that they are not left behind and remain in demand by the public, as well as marketing strategies in business that must continue to be able to expand market reach and innovate in the products they offer. One of the businesses that implements a marketing strategy by participating in the export program on the Shopee platform to optimize sales and introduce their products to the international scene is Erigo Store. The study aims to determine the strategy and marketing mix carried out by local fashion brand Erigo Store so that they could enter the international market. The main theory used is the theory of segmenting, targeting, positioning and the 4P marketing mix. The research used is a descriptive qualitative approach. Data collection is done by library research or literature study. The results of this research show that the analysis shows that Erigo Store uses a promotional strategy to follow the bazaar, create an official erigo website, endorse influencers, sell through various e-commerce, advertising through billboards, promotion through TikTok, and overseas expansion.